Hubungan Tipe Kepribadian dengan Sikap Remaja Pria Tentang Merokok di SMK 2 Yogyakarta - Nur Indah Febriliana, Purwanta, Dwi Harjanta (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: The age for the initiation of smoking tends to be younger every year. The result of a study shows that the initiation of smoking tends to be less than 20 years of age. Whereas according to another study in four of Senior high schools of Yogyakarta randomly chosen, the proportion of male smokers (trial and active smokers) is equal, i.e. 28.3%. There are factors which cause teenagers to smoke, one of which is personality factor. This study observes the relationship between types of personality (extrovert, introvert and ambivert) and attitude about smoking among male teenagers.Objective: To identify the relationship between types of personality and attitude of male teenagers about smoking at SMK 2 of Yogyakarta.Method: This was a survey with cross sectional design. There were as many as 59 respondents consisted of 30 respondents of grade I and 29 respondents of grade II chosen using proportionate stratified random sampling technique. Instruments of the study were questionnaires and data analysis used chi square at deviation=2.Result: There were 31 students of ambivert personality (52.5 %). The majority of respondents had positive attitude about smoking, i.e. 33 respondents (55.9%). Students of introvert personality tended to have positive attitude as many as 14.625 times higher than those of extrovert personality. The result of data analysis showed that X2=9.323 and p=0.009with N=59, deviation=2. When p<0.05 CI95%, HO was denied. Therefore since p=0.009 and p<0.05, HO was denied. Accordingly it could be concluded that there was relationship between types of personality and attitude of male teenagers about smoking.Conclusion: There was relationship between types of personality and attitude of male teenagers about smoking at SMK 2 of Yogyakarta.Keywords: extrovert, introvert, ambivert, attitude, smoking, teenagers